"Discrimination", the Main Concern of Iranian Nurses over Inter-Professional Collaboration: an Explorative Qualitative Study - Leila Valizadeh; Vahid Zamanzadeh; Alireza Irajpour; Masoumeh Shohani (Journal of Caring Sciences, 2015)
Introduction: People in various professions may face discrimination. In the nursing field, discrimination among nurses in the workplace, regardless of race, gender or religion have not been studied; a problem that leads to a reduction in the quality of nursing care and nurse turnover. Discovery of the concerns of nurses about inter-professional collaboration is the purpose of this study. Methods: The present study is conducted by using a qualitative content analysis. The data collection process included 22 unstructured and in-depth interviews with nurses between April 2012 and February 2013 in the medical teaching centers of Iran. A purposive sampling method was used. All interviews were recorded, typed, and analyzed simultaneously. Results: The category obtained from explaining nurses' experiences of inter-professional collaboration was "discrimination" that included two subcategories, namely (1) lack of perspective towards equality in authorities, and (2) professional respect and value deficit.Conclusion: Nurses' experiences are indicating their perception of discrimination that influences the collaboration between nurses, which should be taken into account by managers. The findings of the present study help to managers about decision making on how to deal with staff and can be helpful in preventing nurse turnover and providing better services by nurses.